A single clonal lineage of transmissible cancer identified in two marine mussel species in South America and Europe - Yonemitsu, Marisa A; Giersch, Rachael M; Polo-Prieto, Maria; Hammel, Maurine; Simon, Alexis; Cremonte, Florencia; Avilés, Fernando T; Merino-Véliz, Nicolás; Burioli, Erika AV; Muttray, Annette F; Sherry, James; Reinisch, Carol; et al. (eLife, 2019)
Transmissible cancers, in which cancer cells themselves act as an infectious agent, have been identified in Tasmanian devils, dogs, and four bivalves. We investigated a disseminated neoplasia affecting geographically distant populations of two species of mussels (Mytilus chilensis in South America and M. edulis in Europe). Sequencing alleles from four loci (two nuclear and two mitochondrial) provided evidence of transmissible cancer in both species. Phylogenetic analysis of cancer-associated alleles and analysis of diagnostic SNPs showed that cancers in both species likely arose in a third species of mussel (M. trossulus), but these cancer cells are independent from the previously identified transmissible cancer in M. trossulus from Canada. Unexpectedly, cancers from M. chilensis and M. edulis are nearly identical, showing that the same cancer lineage affects both. Thus, a single transmissible cancer lineage has crossed into two new host species and has been transferred across the Atlantic and Pacific Oceans and between the Northern and Southern hemispheres.
Keywords: transmissible cancer; bivalve; bivalve transmissible neoplasia; Mytilus; Mytilus chilensis; Mytilus edulis